2013
DOI: 10.1155/2013/382523
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Clusterin Concentrations May Predict Resistance to Intravenous Immunoglobulin in Patients with Kawasaki Disease

Abstract: Kawasaki disease (KD) is an acute febrile vasculitic syndrome of early childhood often complicated by coronary artery lesion that drastically reduces the quality of life. The study aimed to identify a reliable marker for predicting nonresponsiveness to the first course of intravenous immunoglobulin (IVIG) in KD patients. A total of 63 patients with KD were enrolled in the study (IVIG response, 58; IVIG resistance, 5). Plasma samples were collected before and after IVIG infusion for measurement of biomarkers. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…The biomarkers include patients’ age, illness day, serum markers (including platelet count, erythrocyte sedimentation rate, hemoglobin concentration, C-reactive protein, eosinophil counts, lactate dehydrogenase, plasma level of albumin, alanine aminotransferase, clusterin, and granulocyte colony-stimulating factor), and sonographic gallbladder abnormalities. 42 47 In addition, genetic variations were reported to associate with IVIG resistance in KD patients. The genetic markers include FcγR family, inositol 1,4,5-trisphosphate 3-kinase C ( ITPKC ), caspase-3 ( CASP3 ), CD209, CCR2-CCR5, CCL3L1, interleukin 1 beta (IL-1B) , and platelet-activating factor acetylhydrolase .…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers include patients’ age, illness day, serum markers (including platelet count, erythrocyte sedimentation rate, hemoglobin concentration, C-reactive protein, eosinophil counts, lactate dehydrogenase, plasma level of albumin, alanine aminotransferase, clusterin, and granulocyte colony-stimulating factor), and sonographic gallbladder abnormalities. 42 47 In addition, genetic variations were reported to associate with IVIG resistance in KD patients. The genetic markers include FcγR family, inositol 1,4,5-trisphosphate 3-kinase C ( ITPKC ), caspase-3 ( CASP3 ), CD209, CCR2-CCR5, CCL3L1, interleukin 1 beta (IL-1B) , and platelet-activating factor acetylhydrolase .…”
Section: Discussionmentioning
confidence: 99%
“…The results of 20 studies were combined in this study comprising 18 Asian studies [4, 6, 9, 10, 13, 17, 19, 20, 22, 24–26, 29, 32, 33, 37, 41, 44] and 2 North American studies [18, 38]. Each subgroup analysis showed the results had statistical significance; however, Baek et al [2] reported that ESR and platelet count could not predict IVIG-resistant Kawasaki disease from their statistical meta-analysis, which is contrary to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki disease (KD) is an acute febrile illness associated with vasculitis of early childhood often complicated by coronary artery lesion that signi cantly impair the quality of life [28][29][30]. The study aimed to identify some reliable indicators for predicting nonresponsiveness to the rst course of intravenous immunoglobulin (IVIG) in KD patients [3,17].Developing the early judgment of IVIG-resistant in patients with KD is crucial for earlier and more effective initial therapy in patients [2].Although several predictive biomarkers and genes have been described. There have been no reliable criteria and consistent reported for identifying children most at risk of IVIG-resistant and developing CAL.…”
Section: Discussionmentioning
confidence: 99%